The interpretation of early modern philosophy - Taborsky, Paul, 1964- (Cambridge Scholars Publishing, 2018)
What is early modern philosophy? Two interpretative trends have predominated in the related literature. One, with roots in the work of Hegel and Heidegger, sees early modern thinking either as the outcome of a process of gradual rationalization (leading to the principle of sufficient reason, and to ""ontology"" as distinct from metaphysics), or as a reflection of an inherent subjectivity or representational semantics. The other sees it as reformulations of medieval versions of substance and cause, suggested by, or leading to, early modern scientific developments. This book proposes a rather dif.